Intermediate Algebra: Connecting Concepts through Application

Published by Brooks Cole
ISBN 10: 0-53449-636-9
ISBN 13: 978-0-53449-636-4

Chapter 6 - Logarithmic Functions - 6.5 Solving Exponential Equations - 6.5 Exercises - Page 528: 67


$g^{-1}(x) = \ln_ (\frac{x}{-3.4})$

Work Step by Step

$g(x) = -3.4e^{x}$ Let $g(x) = y$ $y = -3.4e^{x}$ Swap the variables $x$ and $y$ and then solve for $y$ to find the inverse: $x = -3.4e^{y}$ $(e)^{y} = -\frac{x}{3.4}$ $y = \ln (\frac{x}{-3.4})$ $y = \ln_ (\frac{x}{-3.4})$ $g^{-1}(x) = \ln_ (\frac{x}{-3.4}).$
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.